Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 59. Beitrag. Diptera: Chloropidae und Opomyzidae. - Zuska, Jan (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The present paper lists the species of two families of Diptera - Chloropidae and Opomyzidae - collected by the expedition to Albania by Deutsches Entomologisches Institut. The Chloropidae totaled 72 individuals of 16 species, including 14 species found for the first time in Albania and a probably new species of the genus Parectecephala. Three other species of Albania are mentioned conditionally from publications. Cetema neglecta Tonnoir was found for the first time in the Balkan peninsula. The types of this species were examined, and the comparative morphology of the male post-abdomina of Cetema species is discussed. The collection of Opomyzidae numbers 21 individuals of 3 species, all of them new in Albania. Another species is noted for Albania with reference to a different publication.